ARTIFICIAL FEEDING WITH DIFFERENT PROTEIN CONTENT IN SEED CORAL TROUT GROUPER, PLECTROPOMUS LEOPARDUS IN CONTROLLED TANK - Alit, Anak Agung (Indonesian Aquaculture Society (MAI), 2020)
Coral trout grouper seed have high economic value, but the population in nature has started to decline. The purpose of this study was to obtain a good quality of feed on the growth and stability of seeds of coral trout grouper. Research has been done with experiment container used is fiber tank with size 1m³ counted 6 tanks. The test animals used in the study were the grouper seeds from the culture. The treatments were A = protein content in 48% feed, and treatment B = feed pellet import protein content in feed 55%. Coral trout groupers are kept in fiber tanks. Density of each tank 200 etc /m³ The study used a descriptive design with 2 treatments, each treatment repeated 3 times. Data were analyzed by using ANOVA and at the end of the research was done profit ratio analysis. The results showed that both treatments were significantly different (P <0.05) on survival and daily growth (GR). The highest survival and daily growth in treatment B (SR 97.45%; GR 0,26g/ day) followed by treatment A (SR 85,50 %; GR 0,15g/day). From the economic analysis the best profit B/C ratio was 1.51 treatment B, and followed treatment A was 1.09.